2013
DOI: 10.1007/s00431-013-1974-y
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological changes in rotavirus gastroenteritis in children under 5 years of age after the introduction of rotavirus vaccines in Korea

Abstract: Epidemiologic changes in Korea after the introduction of rotavirus vaccine are consistent with changes observed in other countries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 21 publications
2
20
0
Order By: Relevance
“…Although rotavirus vaccines are recommended but not compulsory, the rate of individuals who had received two or three doses of a rotavirus vaccine was reported to be 65.6 % in Seoul and 52.4 % nationwide (2013 Korean National Immunization Survey, http://www.cdc.go.kr ). As a result, the proportion of rotavirus infection among hospitalized children with gastroenteritis has been decreasing remarkably [ 2 , 5 ]. According to a recent Korean Center for Disease Control report ( http://www.cdc.go.kr ), the incidence of rotavirus gastroenteritis was lower than that of norovirus in 2015.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although rotavirus vaccines are recommended but not compulsory, the rate of individuals who had received two or three doses of a rotavirus vaccine was reported to be 65.6 % in Seoul and 52.4 % nationwide (2013 Korean National Immunization Survey, http://www.cdc.go.kr ). As a result, the proportion of rotavirus infection among hospitalized children with gastroenteritis has been decreasing remarkably [ 2 , 5 ]. According to a recent Korean Center for Disease Control report ( http://www.cdc.go.kr ), the incidence of rotavirus gastroenteritis was lower than that of norovirus in 2015.…”
Section: Introductionmentioning
confidence: 99%
“…Regarding the other notable changes in clinical epidemiology after the introduction of rotavirus vaccines, a few studies reported patterns of seasonal change or age change in addition to decreased overall prevalence of rotavirus infection [ 2 , 5 , 10 ]. A delay of the rotavirus season by 2–3 months was observed in Seoul in a multicenter study during 2007–2010 [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…Rotavirus is the most frequently reported, occurring in 40% to 50% patients with CwG before the rotavirus vaccine was introduced [3,5,10,15,17,23,24]. Rotavirus vaccines were introduced in South Korea in 2007, with the vaccination rate reaching 50% in 2009 [32,33]. These vaccines have decreased the rate of rotavirus positivity in patients with CwG, but the total incidence of CwG did not decrease since the incidence of norovirus infections has increased to become the leading pathogen in recent years [4][5][6].…”
Section: Pathogensmentioning
confidence: 99%
“…In addition, most of the phytoviruses that multiply in insect vectors and are transmitted through the circulative mode are classified in families that also contain animal viruses. This is true for family Reoviridae , which includes rotavirus, a major cause of gastroenteritis in humans [ 36 ], family Rhabdoviridae , which notably includes rabies virus [ 37 ], and family Bunyaviridae , which encompasses human pathogens such as Hantaan virus and Toscana virus [ 38 , 39 , 40 ]. Within the family Rhabdoviridae , genomic organization indicates that some plant viruses of genera Nucleorhabdovirus and Cytorhabdoviru s differ from animal viruses of genera Vesiculovirus , Lyssavirus , Novirhabdovirus and Ephemerovirus only by the presence of an additional gene coding for a movement protein, a protein essential for the systemic spread of the virus in the host plant [ 17 , 18 , 37 , 41 ].…”
Section: Close Relatedness Between Plant and Animal Viruses And Evmentioning
confidence: 99%